1984
DOI: 10.1128/aem.47.1.155-159.1984
|View full text |Cite
|
Sign up to set email alerts
|

In vitro ruminal fermentation of organic acids common in forage

Abstract: Mixed rumen bacteria from cows fed either timothy hay or a 60% concentrate were incubated with 7.5 mM citrate, trans-aconitate, malate, malonate, quinate, and shikimate. Citrate, trans-aconitate, and malate were fermented at faster rates than malonate, quinate, and shikimate. Acetate was the primary fermentation product for all six acids. Quinate and shikimate fermentations gave rise to butyrate, whereas malate and malonate produced significant amounts of propionic acid. High-pressure liquid chromatography of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 13 publications
(12 reference statements)
1
33
1
2
Order By: Relevance
“…On the basis of CDD analysis, Agr-R1 and Agr-R2 were identified as the conserved domain of CitA, which is known to be related to the responses of the CitA ⁄ DcuS-like HPK group to environmental concentrations of citrate (CitA) or C 4 -dicarboxylates, such as malate, fumarate, succinate and aspartate and citrate (DcuS) in TCSs (Mascher et al 2006). It has been demonstrated that citrate, malate and fumarate stimulate rumen fermentation (Russell and Van Soest 1984;Asanuma and Hino 2000;Martin et al 2000a), and citrate and malate are rapidly utilized by rumen micro-organisms (Wright 1971;Martin et al 2000b). Citrate would be utilized by Acidaminococcus fermentans and several species of enterobacteria in the rumen (Cook and Russell 1994;Bott 1997).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of CDD analysis, Agr-R1 and Agr-R2 were identified as the conserved domain of CitA, which is known to be related to the responses of the CitA ⁄ DcuS-like HPK group to environmental concentrations of citrate (CitA) or C 4 -dicarboxylates, such as malate, fumarate, succinate and aspartate and citrate (DcuS) in TCSs (Mascher et al 2006). It has been demonstrated that citrate, malate and fumarate stimulate rumen fermentation (Russell and Van Soest 1984;Asanuma and Hino 2000;Martin et al 2000a), and citrate and malate are rapidly utilized by rumen micro-organisms (Wright 1971;Martin et al 2000b). Citrate would be utilized by Acidaminococcus fermentans and several species of enterobacteria in the rumen (Cook and Russell 1994;Bott 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Malate and citrate were extracted from 0.5‐g plant samples with 25 mL of boiling water for 30 min, filtered through a Whatman no. 1 filter paper, centrifuged (10000 × g , 10 min, 25°C), and filtered through a 0.45‐μm membrane filter before HPLC analysis (Russell and Van Soest, 1984; Callaway et al, 1997). Acids were quantified by HPLC using a Shimadzu LC‐10AS liquid chromatograph (Shimadzu Scientific Instruments, Columbia, MD), with the following Shimadzu accessories: RID‐6A refractive index detector, SCL‐10A system controller, SIL‐10A autosampler, C‐R5A integrator, 50‐μL loop, 50°C, and a Bio‐Rad HPX‐87H organic acid column.…”
Section: Methodsmentioning
confidence: 99%
“…The nutritional value of OA is not well understood, but both rumen and liver metabolism have been demonstrated. Ruminal fermentation of OA was demonstrated in vitro by Russell and Van Soest (1984). Citric, malic and aconitic acid disappeared rapidly, but rough calculations on the data presented showed that considerably less net volatile fatty acid (VFA) carbon was recovered from aconitic acid.…”
Section: Organic Acids In Plantsmentioning
confidence: 99%
“…Applying these calculations, OA in the average ley crop contributed~0.4 MJ ME/kg DM. The lower contribution of quinic and malonic acid was based on their slow degradation rate (Russell & Van Soest, 1984) and reported urinary excretion (Martin, 1982).…”
Section: Organic Acids In Plantsmentioning
confidence: 99%